2014
DOI: 10.1093/pubmed/fdt125
|View full text |Cite
|
Sign up to set email alerts
|

Trending now: future directions in digital media for the public health sector

Abstract: Digital media will continue to develop and move from being an add-on to existing activity to being the major vehicle for significant elements of research, data collection and advocacy. It is important that public health leaders fully understand and engage in its development and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 3 publications
2
44
0
Order By: Relevance
“…While specific knowledge measures were not utilized for this study, all four participants who agreed to post content requested the provision of information or resources to guide them -a common practice in the blogosphere [49]. One participant indicated she would write her own post but use the key messages and graphics provided by the research team.…”
Section: "I Really Don't Think We're Changing People's Minds That Arementioning
confidence: 99%
“…While specific knowledge measures were not utilized for this study, all four participants who agreed to post content requested the provision of information or resources to guide them -a common practice in the blogosphere [49]. One participant indicated she would write her own post but use the key messages and graphics provided by the research team.…”
Section: "I Really Don't Think We're Changing People's Minds That Arementioning
confidence: 99%
“…Perhaps most fundamental for effective development of digital communication for behaviour change is the lack of comprehensive evaluation to date (63) . According to Bert et al (74) , the development of applications for disease prevention and health promotion on digital platforms to date have been totally disconnected from the logic of monitoring and control of content both in terms of scientific validity and user understanding.…”
Section: Challenges and Barriersmentioning
confidence: 99%
“…Use of social media is increasing as a tool for health promotion activities to improve health, and researchers have suggested that Public Health leaders should further explore its potential for research and advocacy [11]. This study has shown that whilst some postgraduate students regularly use social media for informal day-to-day communication and sometimes for work, others have little experience of using such methods in either context.…”
Section: Discussionmentioning
confidence: 86%
“…Burke-Garcia and Scally [11] argue that 'digital media' -which incorporate aspects of social media -will become the main vehicle for research and advocacy; public health leaders should seek to understand them in order to reap maximum benefit. Social media, when used in health promotion, should not be seen as an easy solution to the complexities of behaviour change.…”
Section: The Use Of Media and Social Media In Health Promotionmentioning
confidence: 99%